Differentiated instruction in reading in elementary schools: a systematic review - Widya Karmila Sari Achmad; Sidrah Afriani Rachman; Latri Aras; Muhammad Amran (Institute of Advanced Engineering and Science, 2024)
Increasingly diverse learners in today’s classroom might require teachers to implement differentiated instruction (DI) to create an effective learning process. This systematic review provides an overview of how DI was implemented in reading instruction in elementary education. For this purpose, the researchers systematically searched five databases (APA PsycINFO, Education Research Complete, ERIC, Scopus, and Web of Science). Based on the inclusion criteria, 28 empirical studies from 2002 to 2022 were selected for review. To be included in the review, the studies should be empirical, written in English, peer-reviewed, focusing on reading in elementary education, and include students with or without disabilities. The researchers created content coding in Microsoft Excel spreadsheet to extract relevant information from the selected studies. The findings indicated that implementing DI in reading instruction to elementary school students includes differentiation in content, process, and product, increased quality and quantity of explicit reading instruction, assessments informed instructions, and integrating DI with other instructional models. This emphasizes that although differentiation might seem complex, it is possible to implement it in reading instruction.